The views and experiences of service providers in facilitating a positive behaviour programme for at-risk youth in Cape Town schools: the case of the tenterden place of safety - Mathekga, Keneilwe Golden (Department of Public Law, 2025)
Challenging learner behaviour is one of the critical issues facing the South African education system. Problem behaviours such as bullying, substance abuse, school violence, and gangsterism often result in the expulsion or suspension of a learner as a disciplinary measure. However, these punitive approaches can be counterproductive, as they may expose learners to a range of antisocial behaviours, including involvement in criminal activities, putting them at further risk. Many scholars, both local and international, have criticised punitive disciplinary mechanisms and zero-tolerance policies often adopted by schools, arguing that they contribute to what is known as the school-to-prison pipeline. Restorative justice approaches to school discipline are emerging as a widely supported alternative to such measures, as they align well with PBS models. These approaches provide a holistic understanding of problem behaviour by considering the influences of school, family, and community, rather than isolating the problem. The aim of this study was to explore the views and experiences of service providers in facilitating a PBS model, a restorative approach, for learners with challenging behaviour who are at risk of suspension or expulsion. A qualitative approach and exploratory design were employed, allowing participants to share first-hand experiences relevant to the area of investigation. Purposive sampling was used to select ten participants, who were invited to share their views and experiences in facilitating a PBS programme for learners in schools around Cape Town. Data collection involved semi-structured interviews, and the data were analysed thematically using NVivo software. The findings revealed a strong need for restorative justice approaches to school discipline in South Africa. Participants highlighted that traditional punitive and exclusionary measures, which often rely on suspending or expelling learners, predispose children to further antisocial behaviour. The Circle of Courage model, a positive youth development framework based on the pillars of belonging, mastery, independence, and generosity, was identified as one of the restorative justice approaches that can support positive behaviour in school settings. The findings revealed that the manifestation of problem behaviour within a learner is often influenced by several contributory factors, including gang influence, dysfunctional family structures, substance abuse, corporal punishment, and negative peer influence. Bullying, cyberbullying, and the use of dangerous weapons were also found to significantly impact incidents of school violence. To address the growing problem of challenging learner behaviour in schools, the study recommends that school management across educational settings adopt restorative justice practices in their discipline programmes. Additionally, the study advocates for fully resourced schools with the full-time services of professionals such as psychologists, social workers, learning support facilitators, and occupational therapists. This approach aims to address challenging behaviour through a more ecosystemic perspective. The study also recommends smaller classrooms to better manage the often-uneven teacher- learner ratio, which is believed to exacerbate problem behaviour. Furthermore, there should be improvements in the training curriculum for teachers at the university level. This curriculum should incorporate the basic tenets of restorative justice practices in school discipline, as well as effective behaviour management techniques that consider the school, family, and community of the learner. Lastly, the study suggests that various entities and individuals might find these recommendations useful. These include behaviour analysts, therapists, psychologists, social workers, juvenile correctional centres, probation officers, policymakers, basic education departments, and both administrators and teachers.